Gastronomy management: A comparative analysis of the existing management system standards. Issue 2 (6th February 2017) - Bernardo, Merce; Escalante, Raúl; Roca, Joan; Arbussà, Anna
Abstract : Purpose: The purpose of this paper is to analyze and compare the existing management system standards in the gastronomy sector. Design/methodology/approach: On the basis of secondary data, the most implemented management system standards within this sector are analyzed, namely, the ISO 9001 focusing on the sector of "hotels and restaurants, " the ISO 22000, the "Q" Spanish tourism-specific standard, and the Michelin stars system. Findings: The results, although descriptive, show the differences among them. Regarding the content, the main difference between the documented management system standards and the Michelin stars system is in the evaluation and certification process, as it is known and planned in the former group but not in the latter. The scope is also different, as the former group refers mainly to the process and the latter to results. The diffusion results confirm the increase in sectoral management system standards. Originality/value: Although studies analyzing the importance of sectoral standards have been published, this study is one of the first focusing on four different management system standards in the gastronomy sector. Implications for both practitioners and academia are also discussed.